Efeitos da farinha liofilizada da semente de abacate (Persea americana) em camundongos alimentados com dieta hiperlipídica - Marques, Amanda Ribeiro (2022)
Introduction: The reduction of food waste, the use in its entirety and the adoption of efficient conservation processes, such as lyophilization, are themes that represent the basis for sustainability and food safety. In this sense, it is interesting to investigate the Persea americana, or avocado, which has increased waste by discarding the peel and seed. Some authors carried out the characterization of its seed and found the presence of biologically active compounds, which in experimentation showed hypoglycemic, hypolipidemic, anti-inflammatory and antioxidant effects, thus being able to be used as coadjuvants in the treatment of various diseases. Objectives: To evaluate the effects of freeze-dried avocado (Persea americana) seed meal in mice fed a high-fat diet. Methodology: The seeds were freeze-dried and ground to a flour point, with subsequent centesimal characterization. For the experimental design, Swiss mice were divided into control groups (Nuvilab group/Nuvital® diet; AIN93M group/ AIN-93M diet; High Fat group/ high fat diet) and experimental groups (F0.5, F1 and F2/ high fat diet with addition of freeze-dried flour at concentrations of 0.5%, 1% and 2%, respectively), evaluated for 13 weeks. The oral glucose tolerance test and insulin sensitivity test were performed, followed by euthanasia, and material was collected to quantify adiposity, fasting glucose, insulin, total cholesterol and fractions. Histological analysis of the liver, pancreas and epididymal adipose tissue was performed. Results were expressed as mean±standard error (p≤0.05). Results: In the proximate evaluation of the freeze-dried flour, the moisture content was low and the amount of total carbohydrates was high.,And also, it showed having a good amount of protein high amount of protein and high antioxidant activity from bioactive compounds, with low levels of fat. In the composition of fatty acids, there was a predominance of saturated, but a good concentration of polyunsaturated and essential acids. In the experimental design, the F0.5 group obtained greater weight gain (p<0.001) when compared to normolipidic control groups. This result also occurred in the parameter of weight of the cushions (p<0.05) and adiposity index (p<0.05). As for the lipid profile, there was no difference in the triglycerides parameter, but when analyzing total and non-HDL-c cholesterol, higher values (p<0.001) were observed in relation to controls. In the glucose profile, the highest values (p<0.001) belonged to the High Fat control and all experimental groups, similar to the results of the oral glucose tolerance test, where F2 was higher (p<0.05) than Nuvilab and AIN93M in all times, which was repeated in the insulin sensitivity test, but the difference occurred only in relation to Nuvilab (p<0.05). Regarding the area of adipocytes, there was no statistical difference in the comparison between the groups (p=0.12). There were changes in the liver analysis in the experimental groups (steatosis, lobular inflammation, ballooning, apoptosis and Mallory bodies). In the pancreas, only F1 and F2 presented hypotrophy of the islets of Langerhans. Conclusion: The freeze-dried avocado seed flour has an important composition n nutrients and bioactive compounds, but at the concentrations used, it was not possible to observe positive results in the analyzed parameters, thus requiring further studies using higher concentrations.